Effects of Postinjection Application with Late Partially Premixed Combustion on Power Production and Diesel Exhaust Gas Conditioning. (7th June 2011) - Jeftić, Marko; Yu, Shui; Han, Xiaoye; Reader, Graham T.; Wang, Meiping; Zheng, Ming
Abstract : The effects of postinjection with late partially premixed charge compression ignition (PCCI) were investigated with respect to diesel exhaust gas conditioning and potential power production. Initial tests comparing postinjection application with PCCI to that with conventional diesel high temperature combustion (HTC) indicated the existence of similar trends in terms of carbon monoxide (CO), total unburned hydrocarbon (THC), oxides of nitrogen (NO x ), and smoke emissions. However, postinjection in PCCI cycles exhibited lower NO x and smoke but higher CO and THC emissions. With PCCI operation, the use of postinjection showed much weaker ability for raising the exhaust gas temperature compared to HTC. Additional PCCI investigations generally showed increasing CO and THC, relatively constant NO x, and decreasing smoke emissions, as the postinjection was shifted further from top dead center (TDC). Decreasing the overall air-to-fuel ratio resulted in increased hydrogen content levels but at the cost of increased smoke, THC and CO emissions. The power production capabilities of early postinjection, combined with PCCI, were investigated and the results showed potential for early postinjection power production.